PENERAPAN PENGENDALIAN UMUM DAN PENGENDALIAN APLIKASI DALAM PENCAPAIAN TUJUAN PEMBELIAN PADA PT USDA SEROJAJAYA BATAM - Dian Pratiwi; Firdaus Hamta (Universitas Riau Kepulauan, 2015)
Issues examined in this study are: how the application of general control and application control in achieving the purpose of purchasing the PT. Usda Seroja Jaya Batam. These results indicate that the Overall Application of General Control on Pt.Usda Seroja Jaya Batam has been very good. Can be seen in terms of organization are part of related parts such as Warehouse and purchases, and purchases Planner, Marketing and Purchasing, Finance and Purchasing, Documentation Control as Item Request Form, Form ordering goods, Payment Filing with the letter and Invoice, Asset Accountability enough good, but there is no review by an independent party and that slightly reduce the quality of the company. Application control is applied not in accordance with the existing theory, there is still much to be met by companies such case the use of the security system. But so far applied control is good enough.